Laminate for transparent hygroscopic ptp
A transparent hygroscopic laminate with hydrotalcite and specific resins addresses moisture resistance and transparency issues in packaging, ensuring content stability and safety by absorbing moisture without volatile agents.
Patent Information
- Application Number
- JP2023109480
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-03
- Publication Date
- 2025-01-17
AI Technical Summary
Conventional packaging materials lack sufficient moisture resistance, transparency, and stability, leading to potential deterioration of contents due to moisture absorption, and often require volatile rust-preventing agents that can adhere to the contents or pose ingestion risks.
A transparent hygroscopic laminate comprising a base layer and a hygroscopic layer with hydrotalcite as the moisture absorbent, a binder resin, and specific resin compositions to maintain transparency and moisture absorption, without volatile agents, ensuring a simple layer structure and high hygroscopicity.
The laminate effectively absorbs moisture, maintaining transparency and preventing content deterioration, while eliminating the need for desiccant pouches and volatile agents, enhancing visibility and safety.
Smart Images

Figure 2025007829000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a transparent, moisture-absorbing push-through package (PTP) laminate that is transparent and has moisture-absorbing properties for suppressing moisture absorption of packaged contents, and to a transparent, moisture-absorbing PTP packaging material and a transparent, moisture-absorbing PTP packaging body prepared using the transparent, moisture-absorbing PTP laminate. The transparent moisture-absorbing PTP laminate of the present invention can be applied to products in various fields that dislike moisture. For example, it can be suitably used as a packaging material for preventing rust on metal products such as vehicle screws, shafts, and metal plates, and electrical components, and as a packaging material for suppressing deterioration due to moisture in foods, medicines, and the like. [Background technology]
[0002] PTP packaging, SP packaging, blister packaging, etc. are widely used for packaging medicines and foods that are sensitive to moisture, but many of the conventional products have insufficient moisture resistance. To compensate for this, aluminum foil pillow bags are used as outer bags and desiccants are also included. However, these products do not provide sufficient moisture resistance after the outer packaging is opened, and there have been many accidents where the desiccant is accidentally ingested when it is packed in the package. Therefore, packaging bags have been developed for the purpose of transporting or long-term storage of medicines and food. Furthermore, there is a demand for packaging materials that have more stable moisture-proof, waterproof and barrier properties and that have a simple layer structure and can be produced through a manufacturing process with a small number of steps so as to maintain the quality of the medicines and food contents. For example, Patent Documents 1 to 3 propose packaging laminates in which a highly volatile rust inhibitor that volatilizes at room temperature and exerts a rust-preventing effect is contained in a resin for the purpose of preventing rust on metal product contents. However, there are concerns that the rust-preventive agent may have effects other than the rust-preventive effect, such as the need for a sealed exterior, deterioration of the contents or functional impairment if the vaporized rust-preventive agent comes into contact with the contents, and removal is also troublesome, limiting its uses. Therefore, there is a demand for rust-preventive laminates that do not use volatile rust-preventive agents. In order to improve the moisture resistance of PTP or blister packaging materials, Patent Document 4 proposes incorporating a desiccant or a barrier layer into the packaging material. However, the transparency of the packaging material is insufficient, and the visibility for checking the deterioration state of the contents is poor. In addition, it has been proposed in Reference 5 to incorporate a moisture absorbent of approximately 100 nm in size into a packaging material to increase transparency. However, the moisture absorbent causes secondary aggregation, making it difficult to obtain high transparency. In addition, in order to increase transparency, the content of the moisture absorbent must be reduced, making it difficult to obtain sufficient moisture absorption capacity. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2010-254350 A [Patent Document 2] JP 2007-308726 A [Patent Document 3] JP 2010-052751 A [Patent Document 4] Patent No. 5429948 [Patent Document 5] JP 2021-147086 A Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention solves the above problems, and has excellent manufacturability, a simple layer structure, excellent moisture absorption, and excellent transparency both before and after moisture absorption, thereby providing excellent visibility of the contents. The objective of the present invention is to provide a transparent, moisture-absorbing PTP laminate that can block moisture from the outside and absorb moisture in the space of the packaged content storage section to prevent the contents from deteriorating due to moisture during transportation and long-term storage, and to provide a transparent, moisture-absorbing PTP packaging material and a transparent, moisture-absorbing PTP packaging body produced using the transparent, moisture-absorbing PTP laminate. [Means for solving the problem]
[0005] As a result of various investigations, the present inventors have found that the above object can be achieved by a transparent moisture-absorbing laminate for PTP comprising at least a moisture-absorbing layer containing a specific moisture absorbent and a specific binder resin. That is, the present invention is characterized in the following points. 1. A transparent moisture-absorbing PTP laminate having at least a base layer and a moisture-absorbing layer, The moisture absorbing layer contains at least a moisture absorbent and a binder resin, The moisture absorbent is hydrotalcite, The content of hydrotalcite in the moisture absorption layer is 0.5% by mass or more and 70% by mass or less, In moisture absorption treatment at 25℃50% for 11 days, Moisture absorption: 2.8g / m 2 That's all. The total light transmittance before and after the moisture absorption treatment is 60% or more and 99% or less. The haze before and after moisture absorption treatment is 10% or more and 85% or less. A transparent moisture absorbing PTP laminate characterized by: 2. The transparent, moisture-absorbing PTP laminate described in 1 above, characterized in that the base layer contains one or more materials selected from the group consisting of polyvinyl chloride (PVC), polyvinylidene chloride (PVDC), and cyclic olefin copolymer (COC). 3. The transparent, moisture-absorbing PTP laminate according to claim 1 or 2, wherein the binder resin contains a polyolefin resin. 4. A transparent, moisture-absorbing laminate for PTP according to any one of 1 to 3 above, characterized in that it contains an antioxidant other than a phenol-based antioxidant. 5. The transparent moisture-absorbing PTP laminate according to any one of 1 to 4 above, further comprising a heat seal layer adjacent to one or both sides of the moisture-absorbing layer. 6. A transparent, moisture-absorbing PTP packaging material produced from the transparent, moisture-absorbing PTP laminate according to any one of 1 to 5 above. 7. A transparent, moisture-absorbing PTP package made from the transparent, moisture-absorbing PTP packaging material described in 6 above. Effect of the Invention
[0006] According to the present invention, it is possible to obtain a transparent moisture-absorbing PTP laminate that has excellent manufacturability, has a simple layer structure, yet has excellent moisture absorption properties, and has excellent transparency both before and after moisture absorption, thereby providing excellent visibility of the contents, blocks moisture from the outside, absorbs moisture in the packaged contents storage space, and can suppress deterioration of the contents due to moisture during transportation and long-term storage, as well as a transparent moisture-absorbing PTP packaging material and a transparent moisture-absorbing PTP packaging product produced using the transparent moisture-absorbing PTP laminate. By using the transparent moisture absorbing PTP package of the present invention in a PTP package for medicine, deterioration and discoloration of the medicine can be suppressed. In addition, there is no need to include a moisture absorbing sachet containing silica gel or the like, and the risk of accidentally ingesting the moisture absorbing sachet can be avoided. Furthermore, the risk of losing tablets, dropping them, or identifying broken tablets can be reduced. Furthermore, when the contents are metal products such as metal equipment, the occurrence of rust on the metal products can be prevented, eliminating the need to protect the metal products with oiled paper or the like that has been used conventionally. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of the layer structure of a transparent moisture-absorbing PTP laminate and a transparent moisture-absorbing PTP packaging material of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing an example of another embodiment of the layer structure of the transparent moisture-absorbing PTP laminate and transparent moisture-absorbing PTP packaging material of the present invention. [Diagram 3] FIG. 1 is a schematic cross-sectional view showing an example of the layer structure of a transparent moisture-absorbing PTP packaging body of the present invention.
[0008] In each drawing, the size and ratio of the components may be changed or exaggerated for ease of understanding. Also, for ease of understanding, parts that are unnecessary for the explanation or repeated reference numerals may be omitted. Although not shown in the drawings, an adhesive layer may be provided between each layer. Furthermore, if necessary, in order to strengthen the adhesive strength (adhesion strength) between each layer, the laminated surfaces of each layer may be previously subjected to a physical surface treatment such as corona discharge treatment, ozone treatment, plasma treatment, glow discharge treatment, sandblasting treatment, etc., or a chemical surface treatment such as oxidation treatment using chemicals. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The transparent moisture-absorbing PTP laminate, the transparent moisture-absorbing PTP packaging material, and the transparent moisture-absorbing PTP packaging body of the present invention will be described in more detail below. Specific examples will be given, but the present invention is not limited thereto. In the present invention, the terms film and sheet are used synonymously, and water absorption or moisture absorption refers to the absorption of gaseous and / or liquid water.
[0010] I. Transparent moisture-absorbing laminate for PTP The transparent moisture absorbing PTP laminate of the present invention is a laminate having at least a base layer and a moisture absorbing layer. The absorbent layer and the base layer may each be a single layer or multiple layers. The moisture-absorbing layer may be a single layer that constitutes a sealant layer having heat-sealing properties, or may have a heat-sealing layer on one or both sides of the moisture-absorbing layer to constitute a sealant layer. The transparent moisture absorbing laminate for PTP of the present invention has a moisture absorbing layer and is therefore capable of trapping water vapor that has passed through. The transparent, moisture-absorbing PTP laminate of the present invention can exhibit transparency both before and after absorbing moisture, such as after being left to stand for 11 days in an environment of a temperature of 25°C and a humidity of 50% RH, or a temperature of 40°C and a humidity of 90% RH to absorb moisture.
[0011] The moisture absorption amount of the transparent, moisture-absorbing laminate for PTP of the present invention is, for example, 2.8 g / m2 when left to stand for 11 days at 25°C and 50% humidity. 2 If the moisture absorption amount is smaller than the above range, it is likely to be difficult to suppress deterioration of the contents, and it is substantially difficult to obtain a moisture absorption amount larger than the above range.
[0012] The transparent, moisture-absorbing PTP laminate of the present invention may further contain an antioxidant other than the phenol-based antioxidant.
[0013] The transparent moisture absorbing PTP laminate of the present invention has a high degree of transparency because the moisture absorbent is fine and the difference in refractive index between the moisture absorbent and the binder resin is small, thereby suppressing interfacial reflection and scattering.
[0014] The lower limit of the total light transmittance of the transparent moisture-absorbing PTP laminate of the present invention is preferably 60% or more, more preferably 80% or more, both before and after moisture absorption. If the total light transmittance is lower than the above range, the transparency is likely to decrease. The upper limit is most preferably 100%, but substantially, it is preferably 99% or less, and more preferably 95% or less. Here, the total light transmittance is based on JIS K7361 (Testing method for optical properties of plastics) This refers to the light transmittance measured using color information measuring equipment etc. according to the method specified in.
[0015] The haze of the transparent moisture-absorbing PTP laminate of the present invention is preferably 85% or less, more preferably 70% or less, and even more preferably 30% or less, before and after moisture absorption. If the haze is larger than the above range, the transparency is likely to decrease. The lower limit is most preferably 0%, but substantially, it is preferably 10% or more, and more preferably 14% or more.
[0016] If the transparent moisture absorbing PTP laminate lacks support (rigidity), it may further include a reinforcing layer.
[0017] The thickness of the transparent moisture-absorbing PTP laminate of the present invention is not particularly limited, but is preferably 200 μm or more and 500 μm or less, and more preferably 250 μm or more and 400 μm or less. If it is thinner than the above range, it is difficult to fully exhibit the moisture absorption effect and the moisture absorption effect resulting therefrom, and if it is thicker than the above range, the moisture absorption effect is not improved so much, and the rigidity of the transparent moisture-absorbing PTP laminate becomes too strong, which tends to make it difficult to use as a packaging material and tends to reduce transparency. The layers constituting the transparent moisture absorbing PTP laminate may be laminated via an adhesive layer or an anchor coat layer.
[0018] <Method of manufacturing transparent moisture-absorbing laminate for PTP> A method for producing the transparent, moisture-absorbing PTP laminate of the present invention will be described below. The method for producing the transparent, moisture-absorbing PTP laminate shown below is one example and is not intended to limit the present invention. The formation and lamination of each layer constituting the transparent moisture-absorbing PTP laminate can be carried out by any method, such as wet lamination, dry lamination, solventless dry lamination, extrusion lamination, T-die coextrusion molding, coextrusion lamination, inflation molding, and the like. When the above lamination is performed, if necessary, the surface of each layer may be subjected to a pretreatment such as corona treatment, ozone treatment, etc. Also, anchor coating agents such as isocyanate (urethane), polyethyleneimine, polybutadiene, and organic titanium, or anchor coating agents such as polyurethane, polyacrylic, polyester, epoxy, polyvinyl acetate, cellulose, and other lamination adhesives may be used as desired.
[0019] For example, a transparent moisture-absorbing PTP laminate having a layer structure of substrate layer / adhesive layer / sealant layer [heat seal layer 1 / moisture-absorbing layer / heat seal layer 2] can be produced as follows. First, a resin composition for the heat seal layer 1, a resin composition for the moisture absorbing layer, and a resin composition for the heat seal layer 2 are formed into films and laminated by a co-extrusion lamination method to prepare a transparent moisture absorbing film for the sealant layer. Then, the resin film for the base layer and the transparent moisture-absorbing film for the sealant layer obtained above are bonded via the resin composition for the adhesive layer to produce a transparent moisture-absorbing PTP laminate. The obtained transparent moisture absorbing PTP laminate can be subjected to secondary processing for the purpose of imparting surface functions such as chemical functions, electrical functions, magnetic functions, mechanical functions, friction / wear / lubrication functions, optical functions, thermal functions, and biocompatibility, within the scope that maintains transparency and moisture absorption properties.
[0020] Examples of secondary processing include embossing, painting, gluing, printing, metallizing (plating, etc.) ), mechanical processing, surface treatment (antistatic treatment, corona discharge treatment, plasma treatment, photochromic treatment, physical vapor deposition, chemical vapor deposition, coating, etc.) Transparent moisture absorbing sealant film can also be subjected to lamination (dry lamination and extrusion lamination), bag making, and other post-processing.
[0021] <About each layer of the transparent moisture-absorbing PTP laminate>
[0022] I-1. Base material layer The base layer preferably contains a polyvinyl chloride resin and / or a cycloolefin copolymer (COC). As the polyvinyl chloride resin, polyvinyl chloride (PVC) and polyvinylidene chloride (PVDC) are preferable. Therefore, it is more preferable that the base layer contains one or more materials selected from the group consisting of PVC, PVDC and COC. By including in the base layer these resins with low moisture permeability, it is possible to prevent deterioration of the packaged items in the PTP packaging body due to moisture absorption.
[0023] The substrate layer may be configured with multiple layers having the same or different compositions, and layers within the substrate layer may be laminated via an adhesive layer. The base layer may be laminated directly to other layers such as a moisture absorbing layer, a heat seal layer, or a reinforcing layer, or may be laminated via an adhesive layer, an anchor coat layer, or the like.
[0024] The total light transmittance of the base layer is preferably 60% or more and 99% or less, more preferably 65% or more and 95% or less. If it is lower than the above range, the transparency of the transparent moisture-absorbing PTP laminate as a whole tends to be poor, and it is easy to make it difficult to visually confirm the contents. It is difficult to increase it above the above range, and the production process and quality control become complicated, which tends to reduce productivity.
[0025] The haze of the base layer is preferably 0% or more and 70% or less, more preferably 0% or more and 30% or less, before and after moisture absorption. If it is higher than the above range, the transparency of the transparent moisture-absorbing PTP laminate as a whole tends to be poor, and it is easy to make it difficult to visually confirm the contents.
[0026] (Polyvinyl chloride resin) Specific examples of polyvinyl chloride resins include PVC, PVDC, vinyl chloride copolymers which are copolymers of vinyl chloride monomers and various polymerizable monomers, vinylidene chloride copolymers which are copolymers of vinylidene chloride monomers and various polymerizable monomers, etc. Among these, PVC and PVDC are preferred.
[0027] (Cyclic Olefin Copolymer (COC)) A cyclic olefin copolymer (COC) is a resin having a cyclic structure obtained by copolymerizing a cyclic olefin monomer with a copolymerizable monomer such as an alkene monomer. Here, each of the cyclic olefin monomer and the alkene monomer may be a single type or a mixture of multiple types. The cyclic olefin copolymer has excellent gas barrier properties and low adsorption properties. The glass transition temperature (Tg) of the cyclic olefin copolymer is not particularly limited, but a temperature of 60° C. or higher and 170° C. or lower is preferable since it is easy to handle as a raw material resin for packaging materials.
[0028] Specific examples of cyclic olefin monomers include bicyclo[2.2.1]hept-2-ene and its derivatives, tricyclo[4.3.0.12.5]-3-decene and its derivatives, tricyclo[4.4.0.12.5]-3-undecene and its derivatives, tetracyclo[4.4.0.12.5]-3-pentene and its derivatives, and tetracyclo[4.4.0.12.5]-3-pentene and its derivatives. Examples of the compound include, but are not limited to, chloro[4.4.0.12.5.17.10]-3-dodecene and its derivatives, pentacyclo[6.5.1.13.6.02.7.09.13]-4-pentadecene and its derivatives, pentacyclo[7.4.0.12.5.19.12.08.13]-3-pentadecene and its derivatives, pentacyclo[6.5.1.13.6.02.7.09.13]-4,10-pentadecadiene and its derivatives, pentacyclo[8.4.0.12.5.19.12.08.13]-3-hexadecene and its derivatives, etc. These compounds may be used alone or in combination of two or more.
[0029] The alkene monomer is preferably an α-olefin monomer. Specific examples of alkene monomers include ethylene, propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, and 4-methyl-1-pentene, and among these, ethylene is preferred. These compounds may be used alone or in combination of two or more kinds.
[0030] The cyclic olefin copolymer is preferably a polynorbornene resin in which a norbornene monomer is used as the cyclic olefin monomer, and more preferably a copolymer of a norbornene monomer and an alkene monomer. Norbornene-based monomers are compounds that have a bicyclo[2.2.1]hept-2-ene (norbornene) skeleton. These norbornene-based monomers may have, as a substituent, a polar group such as an ester group, a carboxyl group, or a carboxylic anhydride group. Of these, the norbornene-based monomer is preferably bicyclo[2.2.1]hept-2-ene (norbornene).
[0031] I-2. Moisture absorption layer The moisture absorbing layer is a layer containing a moisture absorbing agent and a binder resin, and the moisture absorbing agent is dispersed in the binder resin. The moisture absorbing layer is preferably formed from a transparent moisture absorbing film including the moisture absorbing layer, and may further include other layers. The moisture absorbing layer may contain a thermoplastic resin other than the binder resin to the extent that the transparency, moisture absorption property, dispersibility, and the like are not impaired. The content of the moisture absorbent in the moisture absorption layer is preferably 0.5% by mass or more and 70% by mass or less, more preferably 0.5% by mass or more and 70% by mass or less of hydrotalcite as the moisture absorbent, even more preferably 20% by mass or more and 60% by mass or less, and particularly preferably 35% by mass or more and 50% by mass or less. If the amount is less than the above range, the moisture absorbing effect is likely to be insufficient, whereas if the amount is more than the above range, the film formability is likely to be poor.
[0032] There is no particular limit to the thickness of the moisture absorbing layer, but it is preferably 30 μm or more and 150 μm or less, and more preferably 50 μm or more and 100 μm or less. If it is thinner than the above range, it is difficult to fully exert the moisture absorbing effect, and if it is thicker than the above range, the moisture absorbing effect is not improved so much, and the rigidity of the transparent moisture absorbing PTP laminate becomes too strong, which tends to make it difficult to use as a packaging material.
[0033] The moisture absorbent is preferably incorporated into the moisture absorbing layer via preparation of a master batch by melt blending the moisture absorbent with a thermoplastic resin. Specifically, it is preferable to prepare a master batch by melt blending the moisture absorbent with a thermoplastic resin at a relatively high concentration, and then dry blending the master batch with a binder resin to obtain a desired concentration in the moisture absorbing layer. The thermoplastic resin to be melt-blended may be one type or two or more types, and may be the same as the binder resin.
[0034] The content of the moisture absorbent in the master batch is preferably 20% by mass or more and 90% by mass or less, and more preferably 30% by mass or more and 70% by mass or less. Within the above range, it is easy to include a necessary and sufficient amount of the moisture absorbent in the moisture absorbing layer in a dispersed state.
[0035] [Moisture absorbent] There is no particular limitation on the number average particle size of the moisture absorbent. However, in order to obtain stable film-forming properties, the number average particle size of the moisture absorbent is preferably 10 μm or less, more preferably 7 μm or less, and even more preferably 1 μm or less. If it is larger than the above range, the film-forming properties tend to decrease, and the transparency of the transparent moisture-absorbing PTP laminate also tends to decrease. The number average particle size of the moisture absorbent is preferably 0.1 μm or more, as it is difficult to stably obtain a moisture absorbent smaller than the above range. There is no particular restriction on the refractive index of the moisture absorbent, but the smaller the difference in refractive index between the moisture absorbent and the binder resin, the greater the transparency of the moisture absorbing layer and the transparent moisture absorbing PTP laminate. The difference in refractive index between the moisture absorbent and the binder resin is preferably 0.07 or less. In the present invention, the moisture absorbent preferably contains hydrotalcite.
[0036] (Hydrotalcite) The hydrotalcite used as the moisture absorbent in the present invention includes calcined hydrotalcite and a magnesium oxide-aluminum oxide solid solution obtained by further decomposing the calcined hydrotalcite by heating. The refractive index of hydrotalcite is about 1.51 to 1.57. Calcined type hydrotalcite is a compound represented by the following formula, which may further contain bound water. Mg 1-x Al x (OH) 2 (CO 3 ) x / 2 In the above formula, x is a number from 0.1 to 0.4. Magnesium oxide-aluminum oxide solid solution is a compound represented by the following formula, and has a higher hygroscopicity than calcined hydrotalcite. Mg 0.7 Al 0.3 O 1.15
[0037] [Binder resin] The binder resin is required to be a resin capable of dispersing the moisture absorbent, and may have heat sealability. The binder resin preferably contains a polyolefin-based resin, and among polyolefin-based resins, it is more preferable that it contains a polyethylene-based resin, and among polyethylene-based resins, it is even more preferable that it contains linear low-density polyethylene (LLDPE). The refractive index of polyolefin resin is about 1.49 to 1.54. By containing these resins in the binder resin, the moisture absorbent can be dispersed, and stable moisture absorption and transparency can be exhibited.
[0038] (Polyolefin resin) Specific examples of polyolefin resins used as binder resins include polyethylene (PE) resins, polypropylene (PP) resins, polymethylpentene, ethylene-vinyl acetate copolymers, ethylene-ethyl acrylate copolymers, ethylene-acrylic acid copolymers, ethylene-methacrylic acid copolymers, ethylene-methyl methacrylate copolymers, ethylene-propylene copolymers, and mixtures of these resins.
[0039] Specific examples of polyethylene resins include low-density polyethylene (LDPE), medium-density polyethylene (MDPE), high-density polyethylene (HDPE), linear low-density polyethylene (LDPE), and Examples include polyethylene (LLDPE), general-purpose polyethylene (general-purpose PE), and polyethylene (PE) copolymers. Among the polyethylene resins, LDPE, LLDPE, general-purpose PE, PE copolymers, etc. are more preferable, and LLDPE is even more preferable.
[0040] (thermoplastic resin) There are no particular limitations on the thermoplastic resin other than the binder resin contained in the moisture absorbing layer, so long as it does not significantly reduce the moisture absorbent dispersibility of the binder resin or the moisture absorption property or transparency of the transparent moisture absorbing PTP laminate and can withstand use as a packaging material, but it is preferable for the resin to have excellent heat sealability.
[0041] For example, the thermoplastic resin may be a polyolefin-based resin. Among the polyolefin resins, polyethylene resins and polymethylpentene are more preferable. Specific examples of polyethylene resins include LDPE, MDPE, HDPE, LLDPE, general-purpose PE, and PE copolymers. Among the polyethylene resins, LDPE, LLDPE, general-purpose PE, PE copolymers, etc. are more preferable, and LLDPE is even more preferable.
[0042] (Antioxidants) The transparent, moisture-absorbing PTP laminate of the present invention can contain an antioxidant, but since phenol-based antioxidants tend to cause yellowing of the transparent, moisture-absorbing PTP laminate, it is preferable to contain an antioxidant other than a phenol-based antioxidant. Preferred antioxidants include phosphorus-based antioxidants and / or thioether-based antioxidants.
[0043] Specific examples of phosphorus-based antioxidants include ADK STAB PEP-8 (ADEKA), ADK STAB PEP-36 (ADEKA), ADK STAB HP-10 (ADEKA), ADK STAB 2112 (ADEKA), ADK STAB 1178 (ADEKA), ADK STAB 1500 (ADEKA), Irgafos 168 (BASF), and the like.
[0044] Specific examples of thioether-based antioxidants include ADK STAB AO-412S (ADEKA), ADK STAB AO-26 (ADEKA), KEMINOX PLS (Chemipro Chemicals), and RIANOX (Rianlin).
[0045] I-3. Heat seal layer, The heat seal layer contains a heat sealable resin and is a layer having excellent heat sealability. The heat seal layer may contain a moisture absorbent to the extent that the heat sealability is not deteriorated, but the heat sealability is highest when no moisture absorbent is contained, which is preferred. The heat seal layer is preferably laminated adjacent to one or both sides of the moisture absorbing layer.
[0046] The heat seal layer and the moisture absorbing layer may be combined and treated as a sealant layer. The sealant layer is preferably formed from a transparent moisture-absorbing film having the layer structure described above, and may further include other layers.
[0047] (Sealant layer or transparent moisture absorbing film) The thickness of the sealant layer or transparent moisture absorbing film is 50μm or more and 200μm or less so that the transparent moisture absorbing PTP laminate has good heat sealability, appropriate rigidity, and moisture absorption as required. It is preferably 80 μm or less, and more preferably 80 μm or more and 150 μm or less. If it is thinner than the above range, the heat sealability and moisture absorption properties may be insufficient, and if it is thicker than the above range, the heat sealability and moisture absorption properties may not be significantly improved and the rigidity may be too strong, resulting in a decrease in workability.
[0048] The sealant layer or the transparent moisture absorbing film may contain any additives within the range that does not significantly impair the effects of the present invention. Examples of the additives include various resin additives that are generally used to adjust the moldability, productivity, and various physical properties of the resin film, such as antiblocking agents, slip agents, pigments, flow control agents, flame retardants, fillers, ultraviolet absorbers, surfactants, etc.
[0049] Furthermore, the sealant layer or transparent moisture-absorbing film may be subjected to secondary processing in order to impart surface functions such as chemical functions, electrical functions, magnetic functions, mechanical functions, friction / wear / lubrication functions, optical functions, thermal functions, and biocompatibility. Examples of secondary processing include embossing, painting, adhesives, printing, metallizing (plating, etc.), machining, surface treatment (antistatic treatment, corona discharge treatment, plasma treatment, photochromic treatment, physical vapor deposition, chemical vapor deposition, coating, etc.), and the like.
[0050] The moisture absorption amount of the sealant layer or transparent moisture absorbing film is, for example, 2.8 g / m2 under an environment of 25°C and 50% humidity for 11 days. 2 If the moisture absorption amount is smaller than the above range, it is likely to be difficult for the transparent moisture absorbing laminate for PTP to suppress deterioration of the contents, and it is substantially difficult to obtain one with a moisture absorption amount larger than the above range.
[0051] The lower limit of the total light transmittance of the sealant layer or transparent moisture-absorbing film before and after moisture absorption is preferably 60% or more, more preferably 75% or more. If the total light transmittance is lower than the above range, the transparency of the transparent moisture-absorbing PTP laminate is likely to decrease. The upper limit is most preferably 100%, but substantially, it is preferably 99% or less, and more preferably 95% or less. Here, the total light transmittance refers to the light transmittance measured using a color information measuring device or the like according to the method specified in JIS K7361 (Testing method for optical properties of plastics).
[0052] The haze of the sealant layer or transparent moisture absorbing film is preferably 90% or less, more preferably 85% or less, before and after moisture absorption. If the haze is greater than the above range, the transparency of the transparent moisture absorbing PTP laminate is likely to decrease. The lower limit is most preferably 0%, but substantially, it is preferably 10% or more, and more preferably 14% or more.
[0053] (Heat sealable resin) The heat-sealable resin is a resin that has excellent heat-sealing properties. The MFR of the heat-sealable resin contained in the heat-sealable layer is preferably 0.2 g / 10 min or more and 10.0 g / 10 min or less, more preferably 0.5 g / 10 min or more and 7 g / 10 min or less. If it is lower than the above range, the film-forming property and heat-sealing property are likely to be inferior, and if it is higher than the above range, the amount of odorous substances generated due to decomposition of the heat-sealable resin is likely to be high, and yellowing resistance is likely to be inferior.
[0054] Preferred heat-sealable resins include LDPE, MDPE, HDPE, LLDPE, ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer, ethylene-methyl methacrylate copolymer, ethylene-propylene copolymer, etc., and LLDPE is more preferred. Among the LLDPEs, a single-stage polymerization gas phase metallocene LLDPE is more preferred because of its excellent yellowing resistance. Even though it is the same metallocene-based LLDPE, multi-stage polymerization gas phase LLDPE has a wide molecular weight distribution and contains a lot of low molecular weight components with a polystyrene-equivalent weight average molecular weight of 70,000 or less, so it does not have excellent yellowing resistance. The single-stage polymerization gas phase metallocene-based LLDPE is particularly preferably C6-LLDPE.
[0055] (Single-stage polymerization gas phase metallocene LLDPE) Single-stage polymerization gas-phase metallocene-based LLDPE is LLDPE synthesized by single-stage polymerization in the gas phase using a metallocene catalyst, and has less low molecular weight components than LLDPE synthesized by multi-stage polymerization using conventional Ziegler-Natta catalysts.
[0056] LLDPE is classified into types such as C4-LLDPE, C6-LLDPE, and C8-LLDPE, depending on the type of monomer copolymerized with ethylene. C4-LLDPE is a linear low-density polyethylene consisting of a copolymer of ethylene and 1-butene, C6-LLDPE is a linear low-density polyethylene consisting of a copolymer of ethylene and 1-hexene and / or 4-methyl-1-pentene, and C8-LLDPE is a linear low-density polyethylene consisting of a copolymer of ethylene and 1-octene. C4-LLDPE, C6-LLDPE, and C8-LLDPE have molecular structures in which the ethylene-derived polyethylene main chain has side chains with 4, 6, and 8 carbon atoms derived from 1-butene, 1-hexene and / or 4-methyl-1-pentene, and 1-octene, respectively.
[0057] I-4.Adhesive layer The adhesive used in the adhesive layer in the transparent moisture absorbing PTP laminate may be, for example, an adhesive for DL (dry laminate), an adhesive for EC (extrusion coat), an adhesive for non-solvent lamination, or the like. The adhesive may be of any of the following types: heat-curable, ultraviolet-curable, and electron-beam-curable types; and may be in any form, such as aqueous, solution, emulsion, and dispersion types. The adhesive may be in any form, such as film / sheet, powder, and solid. The adhesive mechanism may be any of the following types: chemical reaction, solvent volatilization, thermal melting, and thermal pressure.
[0058] Examples of components that form such an adhesive layer include polyvinyl acetate resins such as polyvinyl acetate and vinyl acetate-ethylene copolymers, polyacrylic acid resins consisting of copolymers of polyacrylic acid and polystyrene, polyester, polyvinyl acetate, etc., cyanoacrylate resins, ethylene copolymer resins consisting of copolymers of ethylene and monomers such as vinyl acetate, ethyl acrylate, acrylic acid, methacrylic acid, etc., cellulose resins, polyurethane resins, polyester resins, aliphatic polyester polyurethane resins, polyamide resins, polyimide resins, polyolefin resins such as LDPE, amino resin resins consisting of urea resins or melamine resins, phenolic resins, epoxy resins, reactive (meth)acrylic resins, elastomer resins consisting of chloroprene rubber, nitrile rubber, styrene-butadiene rubber, etc., silicone resins, inorganic resins consisting of alkali metal silicates, low-melting point glass, etc.
[0059] II. Transparent moisture-absorbing PTP packaging material The transparent moisture-absorbing PTP packaging material of the present invention is a packaging material for a base part having a recess for accommodating contents in a PTP packaging body, which is made from the transparent moisture-absorbing PTP laminate of the present invention.
[0060] III.Transparent moisture-absorbing PTP packaging The transparent moisture-absorbing PTP packaging product of the present invention is a PTP packaging product comprising a cover material and a PTP base material made from the transparent moisture-absorbing PTP packaging material of the present invention. EXAMPLES
[0061] The present invention will be described in more detail with reference to the following examples and comparative examples, but the present invention is not limited to these examples.
[0062] <Ingredients> Details of the raw materials used in the examples are as follows.
[0063] [Resin film for base layer] PVC film 1: PVC film manufactured by Mitsubishi Chemical Corporation, F-9450. Thickness: 240 μm. PVDC film 1: PVDC film manufactured by Mitsubishi Chemical Corporation, F-9254. Thickness: 225μm. PP film 1: PP (polypropylene) film manufactured by Mitsubishi Chemical Corporation, E0025NA. Thickness: 250 μm. COC film 1: TAS-225 manufactured by Taisei Kako Co., Ltd. Three-layer structure of CPP (30 μm thick) / COC (190 μm thick) / CPP (30 μm thick).
[0064] [Moisture absorbent] Moisture absorbent 1: Metal oxide-based moisture absorbent, DHT-4C, manufactured by Kyowa Chemical Industry Co., Ltd. Calcined hydrotalcite (magnesium and aluminum), number average particle size 380 nm, refractive index 1.51. · Moisture absorbent 2: Metal oxide-based moisture absorbent, LT015B, manufactured by Toda Kogyo Co., Ltd. Calcined hydrotalcite (magnesium and aluminum), number average particle size 200 nm, refractive index 1.51. · Moisture absorbent 3: Metal oxide-based moisture absorbent, KW2000, manufactured by Kyowa Chemical Industry Co., Ltd. Hydrotalcite (magnesium and aluminum) solid solution, number average particle size 7 μm, refractive index 1.57. · Moisture absorbent 4: Metal oxide-based moisture absorbent, S-KID ZK50PP, manufactured by Sasaki Chemical Co., Ltd. Calcium oxide. Number average particle size 10 μm, refractive index 1.84.
[0065] [Binder resin] LLDPE1: Prime Polymer LLDPE, SP2020. Density 0.916g / cm 3 , MFR 2.3g / 10min, refractive index 1.50.
[0066] [glue] Adhesive 1: Polyester / polyol adhesive manufactured by Rock Paint Co., Ltd. Mass ratio: Rockbond J RU77T / Adlock H-7 = 10 / 1.
[0067] <Preparation of Masterbatch> [Preparation of Masterbatches 1 to 4] According to the formulation in Table 1, the moisture absorbent and the binder resin were melt-blended to obtain masterbatches 1 to 4 (MB1 to 4).
[0068] [Table 1]
[0069] <Preparation of Resin Composition for Moisture Absorption Layer>
[0070] [Preparation of Resin Compositions 1 to 4 for Moisture Absorption Layer] According to the description in Table 2, the master batch and the binder resin were dry-blended to obtain resin compositions 1 to 4 for the moisture absorbing layer.
[0071] [Table 2]
[0072] <Preparation of film for sealant layer>
[0073] [Preparation of transparent moisture-absorbing film A] Using LLDPE 1 for the heat seal layer 1, resin composition for moisture absorbing layer 1 for the moisture absorbing layer, and LLDPE 1 for the heat seal layer 2, lamination was performed by inflation film formation at 180°C. Next, one surface of the heat seal layer was subjected to a corona treatment to obtain a transparent moisture absorbing film A having the following layer structure. Layer structure: Heat seal layer 1 (15 μm thick, surface corona treatment) / moisture absorption layer (90 μm thick) / heat seal layer 2 (15 μm thick)
[0074] [Preparation of transparent moisture-absorbing films B to C and moisture-absorbing film D] Transparent moisture-absorbing films B to C and moisture-absorbing film D were produced in the same manner as transparent moisture-absorbing film A, except that the type of resin composition for the moisture-absorbing layer and the thickness of each layer were changed as shown in Table 3.
[0075] [Preparation of non-moisture absorbing film E] Using LLDPE1, a film was formed by inflation at 180°C, and one side was subjected to a corona treatment to obtain a non-moisture absorbing film E with a thickness of 60 µm.
[0076] [Table 3]
[0077] (Preparation and evaluation of transparent moisture-absorbing laminate for PTP) [Example 1]
[0078] One side of the PVC film 1 for the base layer was subjected to a corona treatment, and the adhesive 1 was applied to the corona-treated surface to a thickness of 3 μm and dried. The corona-treated surface of the transparent moisture-absorbing film A for the sealant layer prepared above was then bonded to the applied surface to obtain a transparent moisture-absorbing PTP laminate. Then, various evaluations were carried out. Layer structure: PVC film 1 (240 μm thick) / adhesive 1 (3 μm thick) / sealant layer [heat seal layer 1 (15 μm thick) / moisture absorption layer (90 μm thick) / heat seal layer 2 (15 μm thick)]
[0079] [Examples 2 to 9, Comparative Examples 1 to 6] A transparent moisture-absorbing PTP laminate was prepared in the same manner as in Example 1, except that the film for the base layer and the film for the sealant layer were changed according to the descriptions in Tables 4, 5, and 6, and was evaluated in the same manner.
[0080] <Evaluation method>
[0081] [Film forming property] The appearance of the film for the sealant layer was observed with the naked eye, and the presence or absence of defects was evaluated according to the following evaluation criteria. ◯: No wrinkles, bumps, or peeling. Passed. △: There were some wrinkles, bumps, and peeling. Passed. ×: Many wrinkles, bumps, and peeling were observed. Failed.
[0082] [Moisture absorption amount] The film for the sealant layer or the laminate for the transparent moisture-absorbing PTP was cut to a size of 100 mm length x 100 mm width to prepare a test piece. The obtained test piece was left to stand for 11 days in an environment of 25°C and 50% RH, and the weight change of the test piece was calculated as 1 m 2 The amount of moisture absorbed per unit was determined.
[0083] [Total light transmittance and haze] The film for the sealant layer or the laminate for the transparent moisture-absorbing PTP was cut to a size of 50 mm length x 50 mm width to prepare a test piece. The total light transmittance and haze of the test pieces before and after moisture absorption (left to stand for 11 days in an environment of 25°C temperature and 50% RH) were measured using a color information measuring device, a haze meter (HM-150, manufactured by Murakami Color Research Laboratory Co., Ltd.), in accordance with JIS K7361 (Testing method for optical properties of plastics).
[0084] [Water vapor permeability] Using a Hitachi High-Tech Mocon oxygen permeability measuring device, the water vapor permeability of the film for the sealant layer or the laminate for the transparent moisture-absorbing PTP was measured at 40°C and 90% humidity before and after moisture absorption (left to stand for 11 days in an environment of 25°C and 50% RH).
[0085] [Heat resistance] Two test pieces measuring 100 mm long x 100 mm wide were cut out from the transparent moisture-absorbing PTP laminate, and the test pieces were stacked so that the sealant layers faced each other. Using a heat sealer, the test pieces were sealed at 180°C and 1 kg / cm from one of the base layer sides. 2 Heat was applied for 1 second, and the change in appearance was evaluated according to the following criteria. Pass: The transparency was maintained at the same level as before heating. Failed: Whitening and loss of transparency.
[0086] [Table 4]
[0087] [Table 5]
[0088] [Table 6]
[0089] <Summary of Results> All of the examples showed a good balance of high moisture absorption, high transparency (high total light transmittance and low haze) before and after moisture absorption, low water vapor permeability, and high heat resistance. On the other hand, Comparative Examples 1 to 3, which used a moisture absorbent that did not contain hydrotalcite, showed poor transparency, and Comparative Examples 4 to 6, which did not contain a moisture absorbent, showed poor moisture absorption. [Explanation of symbols]
[0090] 1. Transparent moisture-absorbing PTP laminate, transparent moisture-absorbing PTP packaging material 2 Base material layer 3 Adhesive layer 4. Moisture absorption layer 5 Heat seal layer 6 Sealant Layer 7 Transparent moisture-absorbing PTP packaging 8 Transparent moisture-absorbing PTP packaging bottom material 9 Adhesive layer 2 10 Transparent moisture-absorbing PTP packaging lid part
Claims
1. A transparent moisture-absorbing PTP laminate having at least a base layer and a moisture-absorbing layer, The moisture absorbing layer contains at least a moisture absorbent and a binder resin, The moisture absorbent is hydrotalcite, The content of hydrotalcite in the moisture absorption layer is 0.5% by mass or more and 70% by mass or less, In a moisture absorption treatment at 25°C and 50% humidity for 11 days, Moisture absorption is 2.8 g / m 2 That's all. The total light transmittance before and after the moisture absorption treatment is 60% or more and 99% or less, The haze before and after the moisture absorption treatment is 10% or more and 85% or less. A transparent moisture-absorbing laminate for PTP, characterized by:
2. The transparent moisture-absorbing PTP laminate according to claim 1, characterized in that the base layer contains one or more selected from the group consisting of polyvinyl chloride (PVC), polyvinylidene chloride (PVDC), and cyclic olefin copolymer (COC).
3. The transparent moisture absorbing PTP laminate according to claim 1 , wherein the binder resin contains a polyolefin resin.
4. 2. The transparent, moisture-absorbing laminate for PTP according to claim 1, further comprising an antioxidant other than a phenol-based antioxidant.
5. 2. The transparent moisture-absorbing laminate for PTP according to claim 1, further comprising a heat seal layer adjacent to one or both sides of said moisture-absorbing layer.
6. A transparent, moisture-absorbing PTP packaging material produced from the transparent, moisture-absorbing PTP laminate according to any one of claims 1 to 5.
7. A transparent moisture-absorbing PTP package made from the transparent moisture-absorbing PTP packaging material according to claim 6.
Citation Information
Patent Citations
Portable radio communication unit
JP1979029948A
Corrosion inhibitor composition for metal, resin composition comprising the same and molding thereof
JP2007308726A
Rust-proof packaging material
JP2010052751A
Rust-proof packaging material
JP2010254350A
Package
JP2021147086A